Una reflexión sobre los rótulos históricos y la dificultad de nombrar a los grupos étnicos de Pampa-Patagonia y el Chaco - Lidia R. Nacuzzi (Centre de Recherches sur les Mondes Américains, 2017)
The research on indigenous history has not managed to reverse an issue that remains problematic : the difficulty in naming ethnic groups with a demonym that represents them. It appears that the more we advance knowledge of the historical and cultural particularities that hide behind each ethnic label, the more self-evident are the incongruities in reproducing and appealing to the ethnonyms imposed mostly during the colonial period by other groups -indigenous or European- in order to express the alterity, show a contentious interaction or legitimize certain relations of domination. We propose to analyze the naming processes by taking into consideration different historical sources produced during the Conquest and the Colony, as well as the way they were taken up by Ethnography.indigenous history, Ethnography, historical sources, ethnic labels